Inhibition of Hepatitis B Virus (HBV) replication and antigen expression by Brucea javanica (L.) Merr. oil emulsion - Qin, Bo; Shen, Shu; Lai, Juan; Yang, Wei; Feng, Lili; Ding, Jiefeng (Frontiers in Cellular and Infection Microbiology, 2023)
Introduction The seeds of Brucea javanica (L.) Merr. (BJ) have been traditionally used to treat various types of cancers for many years in China. In this study, we systematically investigated a BJ oil emulsion (BJOE) produced from BJ seeds with the purpose of evaluating its antiviral effect against hepatitis B virus (HBV). Methods HepG2.215 (a wild-type HBV cell line), HepG2, and Huh7, transfected with wildtype (WT) or lamivudine-resistance mutant (LMV-MT) HBV replicon plasmids, were treated with different doses of BJOE and then used for pharmacodynamic evaluation. Cell viability was determined using CCK8 assay. The levels of HBsAg/HBeAg in cell cultured supernatant, HBcAg in cell lysis solution, and HBV DNA in both were evaluated. Results BJOE at ≤5 mg/ml was nontoxic to carcinoma cell lines, but could significantly inhibit WT/LMV-MT HBV replication and HBs/e/c antigen expression in a dose-dependent manner by upregulating interleukin-6 (IL-6), demonstrating that it possesses moderate anti-HBV activity. As one of the major components of BJOE, bruceine B was found to play a dominant role in IL-6 induction and HBV inhibition. Discussion Our results demonstrated that BJOE suppressed HBV replication by stimulating IL-6, indicating that it has promising clinical therapeutic potential for both WT and LMV-MT HBV.